Ectopic Supernumerary Tooth as a Nidus for Rhinolith Formation - Mehmi, Namrita; Kairo, Arvind; Singh, Anup; Kumar, Rakesh (Indian Journal of Case Reports, 2019)
Rhinolith is a calcified irregular mass around an exogenous or endogenous nidus. Factors responsible for the formation of rhinolithare chronic inflammation around nidus, deposition of mineral salts and enzymatic activity of bacterial pathogens. We report the caseof a 53-year-old patient with a hard radio-opaque mass in the nasal cavity and complaints of nasal obstruction and foul-smelling nasaldischarge. On imaging, it was found out to be formed around an ectopic single cusp tooth in the nasal cavity and which is rarest.Endoscopic removal was performed and the patient was relieved and asymptomatic after the procedure. Hence, endogenous etiologyof the ectopic supernumerary tooth should be kept in mind.